Pregnancy Recommendations Solely Based on Preclinical Evidence Should Be Integrated with Real-World Evidence: A Disproportionality Analysis of Certolizumab and Other TNF-Alpha Inhibitors Used in Pregnant Patients with Psoriasis - Mario Gaio; Maria Giovanna Vastarella; Maria Giuseppa Sullo; Cristina Scavone; Consiglia Riccardi; Maria Rosaria Campitiello; Liberata Sportiello; Concetta Rafaniello (MDPI AG, 2024)
Treatment for pregnant women with psoriasis is limited by the lack of information typically related to clinical trials. While anti-tumor necrosis factor (TNF) drugs offer therapeutic benefits, their safety during pregnancy is a concern. Notably, certolizumab is comparatively safer than adalimumab, etanercept, infliximab, and golimumab according to the current recommendations. Thus, this study aimed to conduct a pharmacovigilance comparative analysis of maternal and neonatal outcomes associated with certolizumab versus other anti-TNF drugs by using data from EudraVigilance. A descriptive analysis was performed of Individual Case Safety Reports (ICSRs) associated with an anti-TNF drug and related to the pregnant patients with psoriasis from 2009 and 2023, focusing our analysis on the specific pregnancy outcomes and fetal/neonatal disorders. The most common pregnancy-related adverse event was spontaneous abortion, predominantly related to adalimumab and certolizumab. Certolizumab was also reported in cases of caesarean section, gestational diabetes, abortion, fetal death, fetal distress syndrome, pre-eclampsia, and premature separation of placenta. Generally, the findings from our study depicted a safety profile that overlapped for each anti-TNF drug, both in maternal/neonatal outcomes and other adverse events, suggesting no substantial differences between treatments. We advocate for further investigations before making concrete recommendations.